PHYSICOCHEMICAL PROPERTIES AND SOLUBILITY OF CO2 IN AQUEOUS STERICALLY HINDERED AMINO ACIDS (SHAA) - ABD AZIZ, NOR FAIQA (2019)
In the present study, a new solvent based, sterically hindered amino acid salts (SHAA) has been explored in order to evaluate its potential application as a carbon capture agent as well as to find alternative to replace conventional solvent, alkanolamines.